Indicadores externos de digestibilidade em ovinos - Mercia Regina Pereira de Figueiredo (2011)
Four trials were conducted to evaluate the external indicators chromic oxide (Cr2O3), titanium dioxide (TiO2), LIPE ® and NANOLIPE ®, to estimate the apparent digestibility of nutrients and fecal output and feeding behavior in sheep. In the first and second experiment were usedsixteen sheep SRD, average body weight of 41.5 kg fed diets based on silage, sugar cane and Tifton 85 hay, distributed in a completely randomized design with split plots. To estimate fecal output and dry matter digestibility and organic matter were used indicators externalchromic oxide (Cr2O3), titanium dioxide (TiO2) and LIPE®, compared with the total collection. There was no significant difference (P> 0.05) between the chromic oxide and LIPE® to estimate the apparent digestibility of nutrients when compared with the total collection. The indicator, titanium dioxide production overestimated and underestimated the fecal digestibility of nutrients. In the experiment to evaluate the ingestive behavior of animals we obtained the time spent feeding, ruminating and resting. The diets based on hay Tifton had more time feeding and less leisure time compared to the diets of cane sugar. In the third and fourth experiments we used SRD twenty sheep, live weight of 41.5 kg fed diets based on sorghum silage and Tifton 85 hay, distributed in a completely randomized design with split plots. To estimate fecal output and apparent digestibility of nutrients were used the indicatorsexternal chromic oxide (Cr2O3), titanium dioxide (TiO2) and NANOLIPE ®. There was no significant difference (P> 0.05) between the markers chromic oxide, NANOLIPE® when compared with the total collection. Titanium dioxide production overestimated and underestimated the fecal digestibility of nutrients. Ingestive behavior in the animal experiment, we evaluated a method of obtaining times for measurement of parameters relating to animal feeding behavior, and the time of 10 minutes for reliable assessment. There was significant difference (P<0.05) between treatments for time spent on food and leisure, and the time spent on food decreased and increased leisure time for diets based on forage andconcentrate, compared with exclusive diets of roughage. The efficiency of feeding and rumination increased with the addition of concentrate to the diets.